Suitability of Recycled Aggregates for Application in Structural Concrete: Experimental Study - Gyadi, Tado; Basack, Sudip (Journal of Graphic Era University, 2025)
Demolition wastes have been increasing day by day as the age-old concrete structures are to be replaced for a new one. In order to reduce the impact of this demolished concrete in nature, recycling it as coarse aggregates appearsto be a highly sustainable option. Recycled aggregates comprise crushed, graded inorganic particles processed from the materials that have been used in the construction and demolition debris. The aim of this project is to determine the suitability of recycled aggregates for application in structural concrete in terms of strength and serviceability criteria. The initial questions concerning the strength of aggregate and workability enhancement aredue to the associated mortar content. Few tests were conducted on the properties of the new aggregate, such as specific gravity, water absorption, and aggregate crushing value. Properties of concrete such as compression strength, splitting tensile strength, flexural strength, and modulus of elasticity were found out. Finally, the application of recycled coarse aggregates in pavement construction was studied. A brief comparison of the cost efficiency was also evaluated.